Pattern of unnatural deaths during COVID-19 lockdown in comparison with deaths reported during 2019 in Sahiwal city - Shahid Nadeem , Sumaira Sarwar , Humaira Rehman ,Hira Iftikhar , Noman Saleem , Fariha Tariq (Journal of Rawalpindi Medical College, 2021)
Background: Lockdown, a social isolation restriction measure has a direct impact on covid-19 transmission but its effect on unnatural deaths remains unknown. Objective: This study has been designed to observe the effects of covid-19 lockdown on unnatural deaths in Sahiwal by comparing with the same period in 2019. Study design: Descriptive retrospective study. Setting: The study was conducted in mortuary of DHQ Teaching Hospital Sahiwal attached with the Department of Forensic Medicine & Toxicology Sahiwal medical college, Sahiwal. Study Duration: Covid-19 lockdown period from 24th March 2020 to 9th May 2020 and the same period in 2019. Materials and Methods: This study includes 62 cases of unnatural deaths, out of which 23 Cases in 2019 and 39 cases in 2020. We have included age, sex, marital status, area of belonging, manner of death, and cause of death as variables in our study. Results: In total 62 cases, in 2019 there were 15 males and 8 females with a mean age of 37.30±19.55 years and in 2020, there were 27 males and 12 females with a mean age of 32.85±15.16 years. The age group in which most number of deaths occurred was 30-59 years (46.8%). In 2019 majority of victims died due to homicide 15(65.2%) while during the lockdown period 14 (35.9%) victims lost their lives in accidents. Firearm injuries were the cause of death in 11(47.8%) cases in 2019 while in the COVID 19 lockdown period the majority of cases 13 (33.3%) were those who died due to roadside accidents. Conclusions: We could not detect significant difference in the two periods examined with respect to sociodemographic factors, but manner of death was significantly affected.